L'affaire - Johnson, Diane (Dutton, 2003)
Traveling to Europe to learn about her culture and find investment opportunities, successful dot-com executive Amy Hawkins becomes involved in an estate dispute involving the numerous children--many illegitimate--of an avalanche victim.
Keywords: Americans -- France -- Fiction; Bildungsromans.; Rich people -- Fiction; Women travelers -- Fiction; Young women -- Fiction; Frankreich; Alps, French (France) -- Fiction; Bildungsromans; Humorous fiction